TOPICAL BREAST MILK IN UMBILICAL CORD CARE FOR CORD STUMP SEPARATION TIME OF UMBILICAL AND PREVENT INFECTION IN NEWBORN BABIES: CASE STUDY: TOPICAL BREAST MILK DALAM PERAWATAN TALI PUSAT PADA BAYI A UNTUK MEMPERCEPAT PELEPASAN TALI PUSAT DAN MENCEGAH INFEKSI: STUDI KASUS - Aridayanto, Visca; Manurung, Suryani; Natalina, Dorlan (Politeknik Kesehatan Kemenkes RI Jakarta I, 2025)
Infant mortality due to tetanus neonatorum infection is 77 per-1,000 live births. The effect of applying topical breast milk method in cord care can accelerate cord detachment and prevent infection compared to other methods. The purpose of applying topical breast milk is to accelerate cord detachment and prevent infection. The method used is a case study with the inclusion criteria of newborns of full term, normal birth weight, being inpatient with the mother and APGAR score of at least seven or more. The number of respondents in this application amounted to one baby, the time of implementation of the application was carried out three days twice a day (morning and evening), observations were made with observation sheets for signs of infection, and umbilical cord release. The results of the application after three days of treatment showed a change in the umbilical cord, the cord turned blackish in colour with a dry texture and no signs of infection. Conclusion The application of cord care using topical breast milk can accelerate the process of cord detachment and prevent infection.